MODEL REKOMENDASI SISTEM UNTUK MENCIPTAKAN WIRAUSAHAWAN BARU DENGAN MENGGUNAKAN TEKNOLOGI WEB - Eko Budi Setiawan; Angga Setiyadi (SINTECH (Science and Information Technology) Journal, 2021)
This research aims to increase the revenue sector of the creative industry by increasing the number of new entrepreneurs created, especially on the MSME scale, as well as to help prospective entrepreneurs when planning to open a business sector that has recommended by the circumstances of the surrounding environment. This research model is devoted to the creation of new entrepreneurs that need for allied governments and the community. The results of the research that has done that has obtained a model that consists of hardware and software requirements, system architecture using web technology, database models, and calculation models used in providing recommendations. These research models have been validated by stakeholders so that they can implement at a later stage of research.